The interactional principle in digital punctuation. (April 2021) - Busch, Florian
Abstract: While early CMC research already mentioned the repetition and omission of certain punctuation signs as salient features of digital interactional writing (cf. Crystal, 2001; Runkehl et al., 1998; Werry, 1996), the theoretical perspective on punctuation was mostly limited to noting down these phenomena in their deviations from an orthographic norm and interpreting them as emulation of spoken language features. In contrast, this paper adopts a graphocentric approach and argues for investigating digital punctuation with regard to its emergent interactional principle : While the rhetorical principle (marking intonational structures) and the grammatical principle (marking syntactical structures) of punctuation are well known in the history of writing (cf. Parkes, 1992), digital punctuation appears as an innovative extension to these functional realms in that it is used by co-participants to shape and organize their mediated interactional order. When punctuation is deployed in an interactional mode, it structures primarily neither intonational patterns nor grammatical patterns, but interactional patterns such as shaping sequential organization and stance-taking. Drawing on a data set of 47 text-messaging threads by German adolescents, the paper investigates the interactional principle of punctuation by frequency analyses as well as by in-depth sequential analyses of <.>, <:>, <!>, <?>, and <…>. The findings suggest that even punctuation signs whose codification in descriptive and prescriptive grammars is based on pure syntactic criteria are utilized to achieve interactional goals. It shows that by following the interactional principle, punctuation establishes collaborative interactional management and serves participants as a graphic means of communicative and social contextualization in digital interactions.